In vitro ZnCl2 cytotoxicity and genotoxicity in human leukocytes: Zero-order kinetic cellular zinc influx (Acta Scientiarum. Health Sciences, 2015)
Zinc (Zn) is an essential trace element for cellular viability, but concentrations above physiologic level may lead to cellular damage. The purpose of the present study was to evaluate the in vitro ZnCl2 genotoxicity and cytotoxicity in human leukocyte cells. This was assessed in an unprecedented way that correlated the level of intracellular Zn after cell exposition with the cellular damage. The exposure to increased Zn concentrations (2.5-20 µg mL-1), showed significantly reduced cellular leukocyte viability. However, significant DNA damages were observed only when the Zn exposure concentrations were from 10-20 µg mL-1. The Zn intracellular levels found in leukocytes was from 72.25-268.9 Ïg cell-1, starting to induce cytotoxicity and genotoxicity at concentrations of 95.68 and 126.2 Ïg cell-1, respectively. The relationship between the exposure concentration and intracellular levels of Zn suggests that the influx of Zn, in the form of ZnCl2, occurs in human leukocytes under zero-order kinetics.